2017
DOI: 10.1590/0102-6720201700030013
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Manometry for the Selection of Obese People Candidate to Sleeve Gastrectomy

Abstract: Background:Sleeve gastrectomy may alter esophageal motility and lower esophageal sphincter pressure. Aim:To detect manometric changings in the esophagus and lower esophageal sphincter before and after sleeve gastrectomy in order to select patients who could develop postoperative esophageal motilitity disorders and lower esophageal sphincter pressure modifications. Methods:Seventy-three patients were selected. All were submitted to manometry before the operation and one year after. The variables analyzed were: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 31 publications
0
22
1
1
Order By: Relevance
“…Thirty-seven articles were fully analyzed, and 21 further articles were excluded. Finally, 16 articles published between February 2013 and September 2019 were included [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], as shown in the PRISMA flow diagram (Fig. 1) [14].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-seven articles were fully analyzed, and 21 further articles were excluded. Finally, 16 articles published between February 2013 and September 2019 were included [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], as shown in the PRISMA flow diagram (Fig. 1) [14].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 194 articles were excluded at this stage because they clearly did not fulfill the eligibility criteria, leaving 51 articles for full-text review. Finally, 27 studies (15 studies for SG ( 23 37 ), 10 studies for RYGB ( 38 47 ), and 2 studies for both surgeries ( 13 , 48 )) were eligible for inclusion in the systematic review and meta-analysis. The flow diagram of the study selection process is shown in Supplementary Item 2, Supplemental Digital Content 4, http://links.lww.com/CTG/A344 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 14 studies ( 13 , 23 27 , 29 33 , 36 , 37 , 48 ) (492 patients) and 11 studies ( 13 , 38 40 , 42 48 ) (417 patients) provided information on esophageal manometric changes after SG and RYGB, respectively. LES resting pressure was significantly decreased after SG (MD = −3.55 mm Hg; 95% CI −6.35 to −0.75; I 2 = 93%) but did not change after RYGB (MD = −0.15 mm Hg; 95% CI −0.86 to 0.55; I 2 = 51%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rebecchi et al 17 , no encontraron cambios en EEI y Del Genio et al 8 , con la manometría de alta resolución mostró que la función del EEI no sufría cambios, pero mostró peristalsis ineficaz y mal vaciamiento esofágico, pero sorprendentemente, estos mismos autores informaron incompetencia cardial o hernia hiatal asociada con la presencia de síntomas de reflujo con índice de síntomas aumentado, esofagitis endoscópica y ERGE di novo en el 5,4% de los pacientes. Por el contrario, otros autores 14,[18][19][20][21][22] , han demostrado un efecto nocivo sobre la presión del EEI, lo que indica una disminución de la presión del LES. Burgerhart 14 observó una disminución en la presión de reposo LES de 18,3 ± 9,2 a 11,0 ± 7,0 mmHg (p = 0,02) medida por manometría de alta resolución.…”
Section: Estudios Manométricos Y Monitoreo De Ph áCido Intraesofágicounclassified